Implantable loop recorder follow-up. (14th October 2021) - Pena Mellado, J; Macias, R; Tercedor, L; Alvarez Lopez, M
Abstract: Introduction: Long ambulatory ECG monitoring can be a useful component in the evaluation of the patient with unexplained syncope or syncope with suspected arrhythmic origin, as well as a sensitive tool for detecting asymptomatic spontaneous cardiac arrhythmias or conduction abnormalities in predisposed patients. Purpose: To determine the diagnostic cost-effectiveness of the implantable loop recorder (ILR) in the origin of unexplained syncope in our center. Methods: A retrospective observational study was carried out in a tertiary center, those patients with an ILR between August 2014 and March 2021 were included. Baseline characteristics of the population and their previous ECG, arrythmias detected during follow-up and pacemaker implant rate were evaluated. Results: One hundred twenty-seven patients with a ILR were included (age 67 years, 49.6% males). Most often cause of ILR was unexplained syncope (90.6%) followed by monitoring after TAVI implant (3.9%). Normal LVEF (>50%) was present in 85.6%, and 75.6% had NYHA I functional class. 118 patients (92.9%) presented sinus rhythm at implant time, and 8 (6.3%) presented AF. 12.6% presented first degree atrioventricular (AV) block, 2 patients (1.6%) had presented previously Mobitz Type I AV block and one patient 2:1 block. Left bundle branch block (LBBB) was present in 13.4%, RBBB in 3.1%, LAFB in 9.4%, RBBB+LAFB in 11% and RBBB+LPFB in 2.4%. Median time of follow-up was 21 months. 3rd degree AV block was the most frequent arrhythmia detected (12.1%), followed by >3s pause (8%) and previously unknown AF (2.4%).The patients with syncope who suffered head trauma (33%) presented a higher rate of pacemaker (PCM) implant compared to those without head trauma: 31.6% vs 14.7%. In total, 19.8% PCM rate implant during follow-up. No complications ILR related. Conclusion: In conclusion, long home ECG monitoring with ILR is a powerful and helpful tool to find out or rule out potentially dangerous arrhythmias as cause of syncope, with no complications in our experience. Funding Acknowledgement: Type of funding sources: None.